THE EFFECT OF FACILITIES AND SERVICE QUALITY ON CUSTOMER SATISFACTION OF GAS STATION IN SETU BEKASI, WEST JAVA - Anjas Riseetyawan; Sularto; Agusti Eviana Sari; Badrunsyah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the effect of the effect of facilities and service quality on customer satisfaction of gas station in Setu Bekasi, West Java. This research is quantitative research. The data analysis method used is Structural Equation Modeling-Partial Least Square (SEM-PLS) Smart PLS software version 3. The population in this study were gas station customers 3417308 Setu Bekasi, West Java, which according to Non-Probability Sampling with the Accidental Sampling method, resulting total sample of 353 respondents. The testing stages are validity test, reliability test, inner model includes convergent validity, discriminant validity, composite validity, Cronbach's alpha, outer model includes path coefficient test and hypothesis testing. The finding reveals that the facility has a positive and significant direct effect on Customer Satisfaction, the service quality has a direct and significant positive effect on Customer Satisfaction, and the facility has a direct positive and significant effect on Service Quality. Meanwhile, the facilities and service quality have a positive and significant indirect effect on customer satisfaction. From the results of these studies, it can be concluded that the facilities and service quality have an indirect effect on customer satisfaction, but with the facilities and service quality in accordance with what customers expect, it can create and increase customer satisfaction.